2005
DOI: 10.1016/j.cmet.2005.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in integrin expression during adipocyte differentiation

Abstract: 3T3-L1 preadipocytes require cAMP for maximal differentiation. Microarray analysis reveals that the integrins alpha5 and alpha6 are coordinately regulated by cAMP. alpha5 expression is gradually diminished during adipogenesis, whereas alpha6 is increased. Overexpression of alpha5 in preadipocytes results in enhanced proliferation and attenuated differentiation. Conversely, alpha6 overexpression is without effect. The GTPase Rac is normally inhibited during differentiation. However, overexpression of integrin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
161
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(174 citation statements)
references
References 68 publications
12
161
1
Order By: Relevance
“…4). We focused on integrin-␤1 because its molecular weight was consistent with the band, and previous studies report that integrins are involved in adipocyte differentiation (33)(34)(35). We found that ␣2,6-sialylation of integrin-␤1 in mouse VATs was significantly reduced in HFD mice compared with CON mice (Fig.…”
Section: St6gal1mentioning
confidence: 84%
“…4). We focused on integrin-␤1 because its molecular weight was consistent with the band, and previous studies report that integrins are involved in adipocyte differentiation (33)(34)(35). We found that ␣2,6-sialylation of integrin-␤1 in mouse VATs was significantly reduced in HFD mice compared with CON mice (Fig.…”
Section: St6gal1mentioning
confidence: 84%
“…We used integrin ␣6 as a marker for plasma membrane localization since it had been shown to be highly expressed on the cell surface of white adipocytes (31). Three-dimensional reconstructions of confocal microscopy optical sections showed that FATP1 is expressed throughout BAT and is clearly upregulated following a 12-h cold exposure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several preadipocyte cell lines undergo differentiation on treatment with a standard adipogenic cocktail consisting of IBMX, dexamethasone and insulin 35 . Both IBMX and dexamethasone trigger the activation of protein kinase A by increasing the intracellular concentration of cAMP, thereby promoting adipocyte differentiation 36 .…”
Section: Discussionmentioning
confidence: 99%